5th Biennial Conference on Heart Valve Biology and Tissue Engineering 2012
DOI: 10.5339/qproc.2012.heartvalve.4.74
|View full text |Cite
|
Sign up to set email alerts
|

Marrow Stromal Cell based Stem Cell Based Transcatheter Aortic Valve Implantation: First Experiences in a Preclinical Model

Abstract: Objectives: We investigate the combination of transcatheter aortic-valve implantation (TAVI) and a novel concept of stem cell-based, tissue-engineered heart-valves (TEHV) comprising minimally-invasive techniques for both, cell-harvest and valve-delivery. Background: TAVI represents an emerging technology for the treatment of aorticvalve disease. The utilized bioprostheses are inherently prone to calcific-degeneration and recent evidence suggests even accelerated degeneration resulting from structuraldamage due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…constructs. 9 In particular in the field of heart valve regeneration, several recent preclinical large animal trials involving sheep 14,15,17 and non-human primate models 16 showed promising initial results and underline the potential of this technology for future therapeutic concepts. Given the major complications when using xeno-or homogenic venous valve transplants, Teebken et al 37 investigated for the first time TEVVs based on a homologous decellularized matrix in the ovine model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…constructs. 9 In particular in the field of heart valve regeneration, several recent preclinical large animal trials involving sheep 14,15,17 and non-human primate models 16 showed promising initial results and underline the potential of this technology for future therapeutic concepts. Given the major complications when using xeno-or homogenic venous valve transplants, Teebken et al 37 investigated for the first time TEVVs based on a homologous decellularized matrix in the ovine model.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Also the group of Pavcnik et al reported a minimally invasive transcatheter approach based on a xenogenic bioprosthetic venous valve system with initial promising results. [43][44][45] Therefore, besides the use of an autologous low-invasive cell source (such as BMMSCs), a clinically relevant TEVV concept requires a combination of the tissue engineering technology with minimally invasive delivery methods, which has already been successfully demonstrated for heart valve tissue engineering in the ovine model for the low- 14 as well as the high-pressure system 17 up to 2 months in vivo. Recently, stented TEHVs could also be minimally invasively delivered into the orthotopic pulmonary position of a clinically relevant non-human primate model that shows promising results in vivo with confluent endothelialization and interstitial valve remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to a fabricate artificial scaffold with exact native leaflet shape, structure and flexibility -so there is the possibility of regurgitation in artificial valve construct due to lack of proper coaptation. Compared to 3D porous structures and hydrogels, nanofibrous mesh is more equivalent to leaflet structurally and morphologically (Emmert et al , 2012, Zund et al , 1998.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…During the last years, attempts were made to develop an autologous tissue engineering aortic valve prosthesis that could be implanted percutaneously. 126,127 This device is anticipated to grow and remodel following the changes that occur in the human body, adopt the cellular phenotypes and structural organization of the native valve, and have a physiological function and increased durability. The first results in animals are encouraging; however, additional technological advances are needed to improve the design of the valve, and research is required to confirm the safety and long-term efficacy of the device before having application in the clinical arena.…”
Section: Future Perspectives In Tavr Emerging Tavr Technologiesmentioning
confidence: 99%